Profil Berat Organ Ginjal Hasil Autopsi di Rumah Sakit Bhayangkara Pekanbaru Periode 2016 - 2021 - Aufan Rizmuafa; Dedi Afandi (Jurnal Ilmu Kedokteran, 2024)
In some cases of dead victims, the doctor is expected to be able to estimate the manner of death and other factors that have contributed to the death. One way to get a more systematic analysis of the probable causes of death is to examine how many different organs weigh.  Assessment of the weight of this organ is needed to determine whether the internal organs are at average weight. This study aims to assess the weight profile of the autopsied kidney at Bhayangkara Hospital Pekanbaru for 2016-2021. The research design used was a retrospective descriptive of Visum et Repertum (VeR) data on autopsied death victims at Bhayangkara Hospital Pekanbaru for the 2016-2022 period. The results of this research are that the number of cases of victims who died at autopsy was 163 cases, with a weight of 110.84 grams in the left kidney and 108.15 grams in the right kidney. The sex that performed the most autopsy was male, namely 122 cases with an average weight of the left kidney of 116.15 grams and 112.18 grams of the right. The age range is 26-45 years, with the left kidney weighing 111.31 grams and 109.30 grams of the right kidney.